Psychological Criteria of Adolescent Well-being in the Context of Digital Socialization - E.N. Volkova; G.v. Sorokoumova (Социальная психология и общество)
Objective. Based on the generalization of the results of research on the psychological well-being of the individual, the characteristics of socialization in the digital environment, patterns of development in adolescence, to identify criteria for assessing the well-being of adolescents in the context of digital socialization. Background. The psychological well-being of a teenager in the context of studying the processes of socialization is the systemic integrity of his subjective assessments of satisfaction with the current standard of living, the development of psychological mechanisms of positive functioning in adolescents, positive assessments of the main domains of well-being. The inclusion of a teenager in a digital environment often takes place without the participation and control of parents and teachers, and digital technologies are becoming a new cultural tool for the socialization of adolescents and largely determine the quality of socialization outcomes regardless of the actions of adults. In conditions of a certain shortage of digital competencies and the inability to use traditional criteria for the success of socialization, the search for reliable educational guidelines becomes an important pedagogical task for both parents and teachers. Well-being, both in its objective indicators and in its subjective representations, can be considered as a guideline in assessing the outcomes of digital socialization of modern adolescents. Methodology. Theoretical analysis of the problem of adolescent well-being in the context of the study of socialization. Conclusions. In adolescence, the main contribution to psychological well-being in the context of socialization in the digital environment will be to meet the need for competence and the need for interaction with other people. Throughout adolescence, the dominant importance of personal neoplasms in the formation of well-being will range from independence, "subjectivity of authorship" of younger adolescents, communicative and digital competence of middle adolescents, to the meaningful fullness of the future and the experience of social success in the digital environment of older adolescents. The criteria for the psychological well-being of adolescents in the context of socialization processes in the digital environment will be: prosocial behavior; the level of digital literacy; the amount of screen time; a sense of happiness; optimism; involvement in socially useful activities; trusting relationships with other people; meaningful and targeted fullness of the time perspective.